Trade Union Objectives and Economic Growth - Andreas Irmen; Berthold Wigger (Center for Economic Studies and ifo Institute (CESifo), 2001)
A trade union whose purpose is to raise wages above the competitive level may foster economic growth if it succeeds in shifting income away from the owners of capital to the workers and if the workers' marginal propensity to save exceeds the one of capitalists. We make this point in an overlapping generations framework with unionized labor. Considering a monopoly union which cares for wages and employment, we determine a range of trade union objectives and characterize the aggregate technology so that the union's policy spurs per capita income growth and increases welfare of all generations that adhere to the union.
Keywords: 330; Trade union; overlapping generations; factor shares; endogenous technical change; employment